Art embroidery as a way of formation of aesthetic culture of the future teachers of the fine arts - T.P. Stefanyuk (Academy of Cognitive and Natural Sciences, 2007)
In article ways of formation of aesthetic culture of the future teachers of the fine arts are considered.